Regulatory Impact Assessment Analysis in Traditional Village Regulations as Strengthening Culture in Bali - I Made SARA; Komang Adi Kurniawan SAPUTRA; A.A Ketut JAYAWARSA (Indonesia Strategic Sustainability, 2020)
This study aims to conduct an analysis of the impact of regulations which are important tools that connect regulatory quality, good governance and economic development, namely the Bali-Indonesia Provincial Regulation Number 4 of 2019 concerning Traditional Villages. The scope of this research is carried out at the Bali Provincial Government which allocates a budget for customary villages, and confirms this in the official village, community organizations, and society in general. The research was conducted qualitatively using the Regulatory Impact Assessment method with the Risk Assessment and Uncertainty Analysis methods. The results of all studies are that this Regional Regulation has a profit-loss assessment with a ratio of positive values ??and negative values ??of 7: 3.The overall positive value ratio is in the government, community organizations and indigenous peoples groups, while negative values ??are in groups outside the government. The results of this study recommend the continuing implementation of this regulation by always referring to the interests of the wider community. The enactment of this Regional Regulation provides evidence that it can be used as a fundamental tool in helping local governments to fill the gap between current and ideal conditions.